In-between: The Simultaneity of the Non-simultaneous. (4th July 2022) - Stehr, Nico
ABSTRACT: At a given time, the sum of the layers that make up the phenomenon of society, "consist" of distinct attributes that emerged in different epochs; for example, different generations or indigenous and natural science knowledge. This is the normal state of affairs in modern societies. Society lacks, in this respect, distinctiveness. First, I am describing the twin concept as the idea of the simultaneity of the non-simultaneous as a cultural phenomenon itself, including many specimens, for example, Werner Sombart's stimulating reflections about the social complexity of the social organization of capitalism. Next, I illustrate the concept in more detail, assisted by a brief description of three well-known social science phenomena: (1) the emergence, present and importance of generations as a macro sociological phenomenon, (2) the moralization of the markets as a mix of micro- and macro themes and what I designate as the (3) compartmentalization in everyday that allows for the presence of contradictory beliefs and activities as a genuine micro sociological topic. The discovery of layers of social phenomena as essential attributes of social reality. In closing the paper, I refer to many of the persisting virtues of the in-between concepts in theorizing and in mobilizing methodological caution in social science reasoning.